Pemungutan Pajak Bumi Dan Bangunan Oleh Pemerintah Kota Yogyakarta Kritik atas Peraturan Daerah Kota Yogyakarta Nomor 2 Tahun 2011) - Hakim, Faisal Luqman (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
Since the enactment of Law Number 28 Year 2009 voting Land and Building Tax (PBB), which is the authority of the central government turning to local authorities. So that local governments can levy the PBB must have a local regulation as its legal basis. Actually it is very potential to be able to provide improvements to the original income (PAD). Unfortunately, not all areas are ready to implement. From 492 existing local government, only about 245 local governments that already have a regulation of PBB, 64 local governments are still in the process and 183 local governments have not compiled at all. Local governments are already doing PBB since in 2011 only Surabaya City Government, then in 2012 increased 17 local governments (including the City of Yogyakarta), and in 2013 there are 113 local governments plan, and in 2014 there will be 117 local governments. To be able to pick up PBB Yogyakarta Government issued Regulation Number 2 of 2011, but the contents of this legislation still needs to be improved because there are chapters that give rise to many interpretations, there is also the use of the word/term is confusing and unclear, the inclusion of legislation as a basis law is no longer valid, and there is a conflict with the legislation higher. The articles need to be improved such as in the section 3 Given the points, then Article 1 paragraph 15, Article 1 paragraph 16, Article 1 paragraph 17, and Article 1 paragraph 18, Article 4, Article 16, Article 29, Article 34 , and Article 36.